HUKUM NAFKAH TERHADAP KELUARGA PADA GERAKAN DAKWAH JAMA’AH TABLIGH - Muhamad Bisri Mustofa (Nizham Jurnal Studi Keislaman, 2019)
Since the emergence of the Transnational Da'wah Movement such as the Tablighi Jama'at, it has created contradictions about the Law of Providing both birth and mentality to the family left in the Khuruj fii sabilillah program (Exiting the Way of Allah) to preach the ummah from house to house, mosque to mosque, inviting listen to Muslims (religious lectures) and invite to pray in congregation in the mosque. From the development of Jama'ah Tabligh's missionary movement in Indonesia, this movement has experienced quite rapid development. Not only is the movement that has a strong community, it is marked by the presence of da'wah markers (da'wah centers) in each of the Provinces and Districts of the City. But in the development of the da'wah movement there are several things that become contradictions in the family, in this case the provision of income for children and wives who are left behind when their head of household implements Khuruj fii sabilillah for 3 days, 40 days and 4 months. Therefore, this paper takes the theme of the Law of Livelihood Against Families in the Tabligh Jama Da'wah Movement in a comprehensive manner.